Marriage Guardianship Law in Iraq Before and After Legislative Amendments - Nur Fitrah Al Haqqi (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2026)
Marriage guardianship is one of the pillars of marriage whose position is debated, because the four Sunni mazhab of thought and the Ja’fari mazhab (Shia Ithna Asyariyah) position it differently. Iraq is an interesting study because since 1959 this country has attempted to unify these doctrinal differences into one law, namely Qanun al-Ahwal al-Syakhsiyyah Number 188, which was drafted during the reign of Abd al-Karim Qasim with the active involvement of the Iraqi women’s movement. This study aims to examine the shift in the position and authority of marriage guardianship in Iraq at three legal moments, namely the original law of 1959, the 1963 amendment after the Baath Party coup, and the 2025 amendment that gave the option for Iraqi Moeslems to submit to the codification of family law of the Shia Ithna Asyariyah. Using normative-qualitative methods through legislative analysis and comparative legal studies, this study finds that the 1959 law limits the coercive power (ijbar) of guardians and places the validity of marriages under the supervision of state courts, the 1963 amendment restores some of the guardian’s authority in marriage matters, while the 2025 amendment introduces a parallel legal pathway that allows guardian/religious figure authority to operate with looser judicial oversight. These shifts are then compared with the regulation of marriage guardianship in Indonesia under Law Number 1 of 1974 as amended by Law Number 16 of 2019 and the Compilation of Islamic Law, to draw lessons on how modern states can codify marriage guardianship without sacrificing legal protection for women.